2017
DOI: 10.1111/imm.12847
|View full text |Cite
|
Sign up to set email alerts
|

Novel KIR genotypes and gene copy number variations in northeastern Thais

Abstract: KIR (Killer Immunoglobulin-like Receptor) variants influence immune responses and are genetic factors in disease susceptibility. Using sequence-specific priming PCR, we have previously described the diversity of KIR genes in term of presence/absence in northeastern Thais (NETs). To provide additional resolution beyond conventional methods, quantitative PCR was applied to determine KIR copy number profiles. Novel expanded and contracted KIR copy number profiles were identified at cumulatively high frequencies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Natural killer cells (NK) play a crucial role in the innate defense against tumors and viral infections also contributing to the immune response during chronic HCV infections [4][5][6]. NK cells activity is regulated by stimulatory and inhibitory NK receptors (NKRs) which consist mainly of inhibitory killer Ig-like receptors (KIRs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Natural killer cells (NK) play a crucial role in the innate defense against tumors and viral infections also contributing to the immune response during chronic HCV infections [4][5][6]. NK cells activity is regulated by stimulatory and inhibitory NK receptors (NKRs) which consist mainly of inhibitory killer Ig-like receptors (KIRs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that inhibitory killer Ig‐like receptors (KIRs) are the most polymorphic NK receptors (Mozer‐Lisewska et al., 2016). They can bind specific ligands and exhibit either a stimulatory or an inhibitory effect on NK cells (Chaisri et al., 2018). KIR genes comprise six genes with activating effects (2DS1, 2DS2, 2DS3, 2DS4, 2DS5 and 3DS1), seven genes encoding inhibitory KIR (2DL1, 2DL2, 2DL3, 2DL5, 2DL5null, 3DL1 and 3DL2) and two pseudogenes (2DP1 and 3DP1).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that inhibitory killer Ig-like receptors (KIRs) are the most polymorphic NK receptors (Mozer-Lisewska et al, 2016). They can bind specific ligands and exhibit either a stimulatory or an inhibitory effect on NK cells (Chaisri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses showed that there are A and B haplotypes of the KIR gene organization. More than 50 distinct KIR haplotypes have been identified [ 10 , 11 , 12 ]. The genomic organization of KIR haplotypes contains four framework genes— KIR3DL3 , 3DP1 , 2DL4 and 3DL2 —which are present on all human KIR haplotypes.…”
Section: Introductionmentioning
confidence: 99%